Cell Type-Specific Anti-Viral Effects of Novel SARS-CoV-2 Main Protease Inhibitors - Geiger, Nina; Diesendorf, Viktoria; Roll, Valeria; König, Eva-Maria; Obernolte, Helena; Sewald, Katherina; Breidenbach, Julian; Pillaiyar, Thanigaimalai; Gütschow, Michael; Müller, Christa E.; Bodem, Jochen (International journal of molecular sciences, 2023)
Recently, we have described novel pyridyl indole esters and peptidomimetics as potent inhibitors of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) main protease. Here, we analysed the impact of these compounds on viral replication. It has been shown that some antivirals against SARS-CoV-2 act in a cell line-specific way. Thus, the compounds were tested in Vero, Huh-7, and Calu-3 cells. We showed that the protease inhibitors at 30 µM suppress viral replication by up to 5 orders of magnitude in Huh-7 cells, while in Calu-3 cells, suppression by 2 orders of magnitude was achieved. Three pyridin-3-yl indole-carboxylates inhibited viral replication in all cell lines, indicating that they might repress viral replication in human tissue as well. Thus, we investigated three compounds in human precision-cut lung slices and observed donor-dependent antiviral activity in this patient-near system. Our results provide evidence that even direct-acting antivirals may act in a cell line-specific manner.